ONE APPROACH TO ASSESSING THE SIZE AND CAPACITY OF THE MARKET - Anatoly V. Korotkov (Статистика и экономика, 2016)
The aim of the article is to study the economic and statistical essence and development of methods of calculation of the market’s size and capacity. Described further material is focused on experts on statistics of the market of goods and services, as well as marketers. Evaluation of size and capacity market is an extremely demanded in practice. However, a review of publications, scientific direction of research is the size and capacity of the market is not yet complete. Researchers are working to develop new approaches to the assessment of the market and to develop relevant procedures. Problems arise distinction between the notions of demand and market capacity. Theoretical basis of the research are the provisions of the economic theory, statistics of the market of goods and services, and marketing.